Cell-free mitochondrial DNA in human follicular fluid: a promising bio-marker of blastocyst developmental potential in women undergoing assisted reproductive technology - Yu Liu; Qiuzi Shen; Xue Zhao; Min Zou; Shumin Shao; Jiao Li; Xinling Ren; Ling Zhang (BMC, 2019)
Abstract Background Cell-free mitochondrial DNA (cf-mtDNA) in body fluids has attracted much attention for the purpose of monitoring disease because of the clinical advantages. This study investigated whether the cf-mtDNA content in human follicular fluid samples was associated with oocyte and embryo developmental competence. Methods We collected 225 individual follicular fluid samples from 92 patients undergoing conventional in vitro fertilization (n = 53) or intracytoplasmic sperm injection (n = 39). cf-mtDNA and cell-free nuclear DNA (cf-nDNA) were measured using real-time quantitative PCR for the ND1 and β-globin genes. Multivariate logistic regression and linear regression were used to analyze data. Results The relative cf-mtDNA content (cf-ND1/cf-β-globin ratio) in follicular fluid was significantly lower in the group showing blastocyst development than in the non-blastocyst group (P = 0.030). Additionally, the relative cf-mtDNA content was significantly and positively correlated with the age of the female patient (P = 0.009), while the relative cf-mtDNA content for older women (≥38 years old) with anti-Müllerian hormone (AMH) ≤1.1 ng/ml was significantly higher than in those with AMH > 1.1 ng/ml (P <0.05). The cf-nDNA content was significantly positively correlated with the antral follicle count (P = 0.012), and significantly negatively correlated with both the number of days of stimulation and the total dose of gonadotropin administration (P = 0.039 and P = 0.015, respectively). Neither cf-mtDNA nor cf-nDNA levels in follicular fluid were associated with oocyte maturation, fertilization, or Day 3 embryo morphological scoring. Conclusions The relative cf-mtDNA content in human follicular fluid was negatively correlated with blastulation and positively correlated with the patient age, indicating that it is a promising bio-marker to evaluate oocyte developmental competence.